Pelatihan Pemanfaatan Sistem Pembayaran QRIS Bagi UMKM Yogyakarta - Malika Yaffa Cakra Asmara; Nugraeni Nugraeni (Yayasan Daarul Huda Kruengmane, 2023)
In the current development of digital financial services, QRIS has become a financial service that is currently in great demand by the public. However, QRIS still has risks, especially for UMKM who do not understand the payment system. In this community service activity, an introduction and stages of making QRIS were carried out, as well as solutions and ways to minimize crime for UMKM at Bu Atun and Cimoll Resto Gayam food stalls. The methods used were interviews, direct observation and training. The result of this community service is that UMKM know the benefits and process of making QRIS and understand that QRIS has more benefits for UMKM than the risks they experience.